2019
DOI: 10.21608/ajs.2019.19168.1112
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of anticancer effect of methanolic extract of Artemisia herba alba on human cancer cell lines

Abstract: Artemisia (Asteraceae family) has been reported to possess different bioactive phytochemicals including phenols, sesquiterpene lactones and flavonoids. The aim of this study was to estimate the anti-proliferative activity of the methanolic extract of Artemisia herba alba using in vitro assays on two of human cancer cell lines compared with the normal cell lines. The obtained results indicated that A.herba alba extract showed highly cytotoxic and anti-proliferative effects on tested human cancer cells as reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Our findings align with those of Khlifi et al (2013) , who reported that methanol extract from AHA caused a reduction in cell viability of various human cancer cell lines, including human bladder carcinoma RT112, human laryngeal carcinoma Hep2, and human myelogenous leukemia K-562. In addition, Mohammed et al (2019) demonstrated the significant cytotoxic and anti-proliferative effects of AHA methanolic extract on the e human hepatocellular carcinoma (HepG2) cell line.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings align with those of Khlifi et al (2013) , who reported that methanol extract from AHA caused a reduction in cell viability of various human cancer cell lines, including human bladder carcinoma RT112, human laryngeal carcinoma Hep2, and human myelogenous leukemia K-562. In addition, Mohammed et al (2019) demonstrated the significant cytotoxic and anti-proliferative effects of AHA methanolic extract on the e human hepatocellular carcinoma (HepG2) cell line.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its diverse pharmacological and biological properties, AHA exhibits various beneficial effects, including its potential in antidiabetic ( Bourebaba et al , 2023 ), antimicrobial ( Dif and Fatima Zohra, 2023 ), antitumor ( Mohammed et al , 2019 ), antimalarial, antioxidant ( Mohammed et al , 2021 ), insecticidal, and neurological activities ( Boukraa et al , 2022 ).…”
Section: Introductionmentioning
confidence: 99%